Sumbangan Dan Peranan Azizan Baharuddin Dalam Kelestarian Sains Dan Agama (The Roles and Contributions of Azizan Baharuddin in the Sustainability of Science and Religion) - NUR ASYIKIN HAMDAN; NAZRI MUSLIM; ABDUL LATIF SAMIAN (MALIM: Jurnal Pengajian Umum Asia Tenggara, 2017)
Azizan Baharuddin is a female Malay Muslim who has given significant contributions in the preservation of science and religion in Malaysia. The influence of her ideas is not limited to the local context but has also impacted other Muslim countries as well. Today, a lot of the Muslim people have started to believe in the separation of science and religion which is due to the perception that science has no place in Islam and that the religion rejects science. In reality, there is no contradiction between Islam and science. Thus, this article discusses about Azizan's roles and contributions in preserving science and religion. She believes that the misconstrued belief that science and religion contradict each other can be improved through intellectual discourse, dialogues and campaigns which should be emphasized in the country's education system.